Sulfentrazone efficiency on Ipomoea hederifolia and Ipomoea quamoclit as influenced by rain and sugarcane straw - Correia, N.M [UNESP]; Camilo, E.H; Santos, E.A (Sociedade Brasileira da Ciência das Plantas Daninhas, 2013)
Objetivou-se neste trabalho avaliar o controle em pré-emergência de Ipomoea hederifolia e Ipomoea quamoclit pelo herbicida sulfentrazone em função do intervalo de tempo entre a aplicação e a ocorrência de chuva e da manutenção ou não de palha de cana-de-açúcar na superfície do solo. Três experimentos foram desenvolvidos: dois em casa de vegetação e um em campo. Nos experimentos em casa de vegetação, foram estudadas três doses de sulfentrazone (0, 0,6 e 0,9 kg ha-1) pulverizado em duas quantidades de palha na superfície do solo (0 e 10 t ha-1) e cinco intervalos de tempo entre a sua aplicação e a simulação de chuva (0, 20, 40, 60 e 90 dias). No experimento em campo, foram avaliados cinco tratamentos de herbicida (sulfentrazone a 0,6 e 0,9 kg ha-1; sulfentrazone + hexazinone a 0,6 + 0,25 kg ha-1; amicarbazone a 1,4 kg ha-1; e imazapic a 0,147 kg ha-1) e duas testemunhas sem aplicação. A manutenção ou não da palha de cana sobre o solo também foi estudada. em casa de vegetação, a aplicação de 0,6 kg ha-1 de sulfentrazone foi suficiente para o controle adequado de I. hederifolia e I. quamoclit num ambiente seco com até 90 dias sem chuva após a aplicação. Os 20 mm de chuva simulados após a aplicação do herbicida foram suficientes para remover o sulfentrazone da palha para o solo, pois o efeito biológico de controle de I. hederifolia e I. quamoclit não foi alterado. em campo, sem ou com a permanência de palha de cana sobre o solo, o sulfentrazone isolado (0,6 e 0,9 kg ha-1) ou em mistura com hexazinone (0,6 + 0,25 kg ha-1) foi eficaz para I. hederifolia e I. quamoclit, com resposta similar ou melhor que a do amicarbazone (1,4 kg ha-1) e imazapic (0,147 kg ha-1).

The aim of this study was to assess the capacity of sulfentrazone applied in pre-emergence in controlling Ipomoea hederifolia and Ipomoea quamoclit as a function of the time interval between herbicide application and the occurrence of rain, and the presence of sugarcane straw on the soil surface. Two greenhouse experiments and one field experiment were conducted. For the greenhouse experiments, the study included three doses of sulfentrazone applied by spraying 0, 0.6, and 0.9 kg ha-1, two amounts of straw on the soil (0 and 10 t ha-1), and five time intervals between the application of herbicide and rain simulation (0, 20, 40, 60, and 90 days). In the field experiment, five herbicide treatments (sulfentrazone at 0.6 and 0.9 kg ha-1, sulfentrazone + hexazinone at 0.6 + 0.25 kg ha-1, amicarbazone at 1.4 kg ha-1, and imazapic at 0.147 kg ha-1) and two controls with no herbicide were studied. Management conditions with or without sugarcane straw on the soil were also assessed. From the greenhouse experiments, sulfentrazone application at 0.6 kg ha-1 was found to provide for the efficient control of I. hederifolia and I. quamoclit in a dry environment, with up to 90 days between herbicide application and rain simulation. After herbicide application, 20 mm of simulated rain was enough to leach sulfentrazone from the straw to the soil, as the biological effects observed in I. hederifolia and I. quamoclit remained unaffected. Under field conditions, either with or without sugarcane straw left on the soil, sulfentrazone alone (0.6 or 0.9 kg ha-1) or sulfentrazone combined with hexazinone (0.6 + 0.25 kg ha-1) was effective in the control of I. hederifolia and I. quamoclit, exhibiting similar or better control than amicarbazone (1.4 kg ha-1) and imazapic (0.147 kg ha-1).
Eficácia de sulfentrazone em Ipomoea hederifolia e Ipomoea quamoclit influenciada pela ocorrência de chuva e palha de cana
Keywords: Boral®; cana crua; corda-de-viola; retenção de herbicidas; Saccharum officinarum; Boral®; raw sugarcane; morning glory; herbicide retention; Saccharum officinarum